Usability testing of Google cloud applications: students' perspective - Abdullah Alqahtani (OmniaScience, 2019)
Modern information and communication technologies affect all areas of life significantly, including education and learning. Cloud storage tools are one of the forms of modern information technologies that are employed to serve the educational process. The current research aims to study the use of Google cloud applications (Google Classroom, Google Plus and Google Drive) in education and to determine the most appropriate web-based training environment in view of the level of usability. The experimental method was applied in this study using a sample of 200 students from Imam Abdul Rahman bin Faisal University. The current research found that there was some convergence in the usability of the three environments. Based on the results of the study, it was found that the environment of Google Classroom has the highest usability value (86.45), and also showed statistically significant differences in scholastic achievement in the application the service of Google Classroom in the educational process.